1998
DOI: 10.3406/galip.1998.2156
|View full text |Cite
|
Sign up to set email alerts
|

Circulation des silex dans le nord de l'Aquitaine au Paléolithique supérieur : l'occupation de l'espace par les derniers chasseurs-cueilleurs

Abstract: Pendant le Paléolithique supérieur, dans le nord de l'Aquitaine, les silex ont été transportés sur de grandes distances. Ces circulations de matières premières mettent en relation des régions allant de la Gironde au Massif central suivant un axe est-ouest, le long du bassin de la Dordogne. Ce fait complète le modèle d'occupation de l'espace proposé par R. K White : les sites de la basse vallée de la Vézère sont liés à des abattages massifs de rennes lors de leurs migrations et sont des habitats de mauvaise sai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 2 publications
0
15
0
7
Order By: Relevance
“…1). 21,23 Subsequent research in France by Peyrony, 19 de Sonneville-Bordes, 20 Delporte, 24 and others has shown that the lithic assemblages associated with the split-base "pointe d'Aurignac" are for the most part both highly distinctive and, with some minor, essentially quantitative variations in the relative frequencies of end scrapers and burins, relatively homogeneous in composition: the traditional assemblages of the "Aurignacian I" type, as represented at La Ferrassie layer F, Abri Castanet, Abri Pataud levels [11][12][13][14], and many other sites in western France. 22,24,25 Apart from the splitbase (mostly antler) points, the most diagnostic features of these industries are high frequencies of thick carinate or, more rarely, nosed scrapers shaped by means of distinctive fluted micro-bladelet retouch, combined with varying frequencies of extensively edge retouched "Aurignacian blades" (lames Aurignaciennes) often showing relatively invasive, overlapping retouch, and sometimes approaching the strangulated blade form (Fig.…”
Section: "Classic" Aurignacianmentioning
confidence: 99%
See 1 more Smart Citation
“…1). 21,23 Subsequent research in France by Peyrony, 19 de Sonneville-Bordes, 20 Delporte, 24 and others has shown that the lithic assemblages associated with the split-base "pointe d'Aurignac" are for the most part both highly distinctive and, with some minor, essentially quantitative variations in the relative frequencies of end scrapers and burins, relatively homogeneous in composition: the traditional assemblages of the "Aurignacian I" type, as represented at La Ferrassie layer F, Abri Castanet, Abri Pataud levels [11][12][13][14], and many other sites in western France. 22,24,25 Apart from the splitbase (mostly antler) points, the most diagnostic features of these industries are high frequencies of thick carinate or, more rarely, nosed scrapers shaped by means of distinctive fluted micro-bladelet retouch, combined with varying frequencies of extensively edge retouched "Aurignacian blades" (lames Aurignaciennes) often showing relatively invasive, overlapping retouch, and sometimes approaching the strangulated blade form (Fig.…”
Section: "Classic" Aurignacianmentioning
confidence: 99%
“…21,22 The original, classic "fossile directeur" of this assemblage has always been seen as the so-called split-base point, which, significantly, was generally referred to as the "pointe d'Aurignac" (Fig. 1).…”
Section: "Classic" Aurignacianmentioning
confidence: 99%
“…Evidence from several studies in France (Demars 1982(Demars , 1994Chadelle 1983;Geneste 1985;Meignen 1988;Turq 1996;Lucas 2000;Cole 2002) shows that Middle and Upper Paleolithic stone workers there transported non-local materials mostly in the form of prepared cores and products, and that those products become increasingly well-sorted (homogeneous with regard to kinds of products) with increasing distances from the raw material source. In other words, faced with an array of chipped stone products (flakes, blades, and tools), people transported those that were smaller and more useful.…”
Section: Three Hypotheses and Their Empirical Consequencesmentioning
confidence: 99%
“…A problem with this hypothesis is its reliance on an assumed linkage between form and function, which is no longer accepted as valid. Seeking to resolve this issue, Demars (1982Demars ( , 1989Demars ( , 1994 has argued that blade technology became widespread in certain Upper Paleolithic industries because blades offer an ideal combination of utility and portability, qualities that were valued by mobile Upper Paleolithic hunter-gatherers who often transported their raw material long distances.…”
Section: Introductionmentioning
confidence: 99%
“…La seule industrie qui présente un indice laminaire de l'outillage élevé (ILO = 72,78), habituel pour cette période (Demars, 1994), est celle du niveau 14. Après le niveau 14, c'est le niveau 11 qui présente le plus d'outils sur lame, mais dans des proportions bien moins importantes (ILO = 56,32).…”
Section: Quantification Des Eclats Et Implicationsunclassified